Renal complications to COVID-19 - Rozas-Olivera, Victor Vladimiro (2021)
Patients treated with inhibitors or blockers of the renin-angiotensin-aldosterone system (RAAS), showed no increased risk to develop COVID-19, nor an increased risk to developed a more critical stage of the disease. Patients with COVID-19, at the time of hospitalization showed a high proportion of the presence of proteinuria and hematuria. Reports from Europe and the United States showed that patients with COVID-19, whom required intensive care unit care, had an incidence of acute kidney injury (AKI) of 20% to 40%, and its onset showed a temporal relationship to the initiation of mechanical ventilation. Pathological findings showed that the principal cause of the renal injury was the development of acute tubular necrosis. The surge of patients with COVID-19 and AKI, demanded extraordinary efforts from health systems, to provide specialized medical personal and equipment for dialysis therapy.